Analisis Yuridis Terhadap Hak-Hak Atas Tanah Yang Berada Di Atas Hak Pengelolaan Pelabuhan - Lovelly Dwina Dahen (Jurnal Ilmu Hukum, 2012)
The role of sea ports in the future will be increasingly important, it is necessary to improve the quality of service (quality of services). According to the rules of the Decree of Directors. (Limited) II No Ports Indonesia. HK.56/1/2/PI.II-2000 dated January 3, 2000 submission of the use of portions of land can be provided with a port HPL Broking and Right to Lease the building. This is contrary to the Regulation of the Minister of Interior No.1 of 1977, in which rights can be given to land management rights are Broking and Right to Use.